CORPUS LINGUISTICS STUDY: INVESTIGATING AUXILIARY VERB ON CNN NEWS - Fakhri Muhammad Rahadyan (Faculty of Education and Teachers Training, 2021)
This article uses descriptive data research to determine how many auxiliary verbs were used in news stories included in the article. Thus, the purpose of this paper is to investigate the use of auxiliary verbs in the news section of CNN News in order to determine the frequency of auxiliary verbs and how it relates to the characteristics of news text. This research was compiled. The CNN News corpus, which consists of news articles, belongs to the group of soft news, with a total word count of 923 from 25 pieces of an online news article. The auxiliary verb types used in this study are those compiled in Areeluck Harnmontree’s auxiliary verb compilation.